Uso de almidón de yuca (Manihot esculenta Crantz), camote (Ipomoea batata L.) y arroz (Oryza sativa L.) en la elaboración de un embutido a base de carne de corvina (Cynoscion albus). - León Chang, Keny Jonnsan (2019)
XVII ABSTRACT The objective of this research was to develop a sausage based on fish meat (Cynoscion albus) from the use of cassava starch (Manihot esculenta Crantz), sweet potato starch (Ipomoea batata L.) and rice starch (Oryza sativa L.) that complies with the requirements established by the Ecuadorian Institute of Normalization (INEN). The study was carried out at the Processing Plant of Meat Industries of the Faculty of Technical Education for Development of the Catholic University of Santiago de Guayaquil. The Design Expert 11 program was used, obtaining 11 preliminary formulations, which were processed in triplicate and the sensory analysis was performed with the help of a semi-trained sensory panel of the Nutrition and Dietetics Career of the Institution aforementioned for the determination of the best formulation. The final product was characterized by physical, chemical and microbiological analysis, whose results were compared with the corresponding INEN regulations; in the analyzes performed on the resulting product the following values were obtained: 14.87 % protein, 8.8 % starch, 2.50 % ash and 5.20 % acidity and a count of less than 10 upc /g of fungi, yeasts and absence of pathogens, results that met the required requirements. The cost benefit in the production of the sausage was USD 1.40, which means that, for every dollar invested, a profit of USD 0.40 is gained.